2019
DOI: 10.1177/1066896919858129
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Adult-Onset Diffuse β-Cell Nesidioblastosis and Pancreatic Neuroendocrine Tumor: A Case Report and Review of the Literature

Abstract: Nesidioblastosis is an uncommon cause of organic persistent hyperinsulinemic hypoglycemia in adults. We report a case of adult-onset diffuse β-cell nesidioblastosis in a 49-year-old woman who was status-post Roux-en-Y gastric bypass and distal pancreatectomy for a well-differentiated pancreatic neuroendocrine tumor. While the neuroendocrine tumor was suspected to be an insulinoma, persistent hypoglycemia postoperatively suggested either incomplete resection or a second pancreatic neoplasm. Completion pancreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…The association of these two entities is a rare clinical finding. To the best of our knowledge, the association between nesidioblastosis and neoplastic diseases of the endocrine pancreas has been described in just a few cases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The peculiarity of our case is that the diagnoses of nesidioblastosis and insulinoma were not concomitant.…”
Section: Discussionmentioning
confidence: 54%
“…The association of these two entities is a rare clinical finding. To the best of our knowledge, the association between nesidioblastosis and neoplastic diseases of the endocrine pancreas has been described in just a few cases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The peculiarity of our case is that the diagnoses of nesidioblastosis and insulinoma were not concomitant.…”
Section: Discussionmentioning
confidence: 54%
“…Another point that needs to be kept in mind is the differential diagnosis between NET and neuroendocrine hyperplasia. The latter has a series of major and minor critieria and its diagnosis, especially diffuse hyperplasia, might need near total pancreatectomy [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of an insulinoma by means of macroscopic, microscopic, and immunohistochemical evaluation of the tissue is the last major criterion to diagnose diffuse, adult-onset nesidioblastosis. From our point of view, this is problematic because many patients have been reported that suffered from pathologically detectable insulinoma and concomitant islet cell hyperplasia/nesidioblastosis (also termed “background nesidioblastosis”) [ 16 , 58 , 75 , 109 , 231 , 235 , 283 , 285 , 286 , 316 , 317 ]. One patient was even reported to have an insulinoma relapse, which was possibly related to the coexistence of islet cell hyperplasia/nesidioblastosis [ 231 ].…”
Section: History Histopathological and Clinical Definition Of Hyperin...mentioning
confidence: 99%